The Potential of Using Quizizz Application on English Language Teaching (Conference on English Language Teaching, 2023)
The development of technology in educational world  requires teachers or educators to be able to use  various  kinds  of learning media  in learning and  teaching  activities. There  are many  kinds  of media  which can make  the  learning more  interesting such as Quizizz. This research aims to reveal the potential of this application on English language teaching. This is a systematic review  research. The method used  in this  research is systematic literature review  in the purpose of collecting data from Google Scholar and Proquest. The researches found 30 journal articles that discussed similar topics to this current research. Subsequently, it  could  be  classified  according  to  students’ perception in  the  use  of Quizizz, teachers’ perception in the  utilization of Quizizz, the  use  of Quizizz as assessment tool, the  use  of Quizizz as learning media during pandemic covid-19 and the use of quizizz in general. Thus, this  research showed that  the  Quizizz had  positive  implementation and  good potential in English language teaching  activities.